THE ROLE OF ROLE PLAYING AS A MEANS OF FORMING COMMUNICATION SKILLS - Khodjaeva, Makhliyo (Журнал иностранных языков и лингвистики, 2020)
The article discusses the use of role-playing games in English lessons, which makes it possible to increase the effectiveness of classes. Learning activities become more interesting and varied, game participants actively interact with each other, which allows accelerating the development of speech skills. Role-playing is used to solve complex problems of mastering new material, consolidating and developing creative abilities, as well as for the formation of general educational skills. It enables students to understand and study the teaching material from different perspectives.